Reform of decentralization and regional policy in the Visegrad - Bytyak, Yuriy P.; Irina Bodrova, Svitlana Serohina,; Chyrkin, Anton; Shestopal, Sergey S. (Opción, 2019)
In our work, we highlight how, in particular, territorial changes of public authority have been taking place and analyze the current state of the territorial basis of municipal power (local governance) in the countries under review via comparative qualitative research methods. As a result, it appears that Slovakia, like other Visegrad countries, boasts a high level of territorial fragmentation. In conclusion, the corresponding changes have made it possible for the former post-socialist countries to experience the benefits from structural and regional EU policies through cooperation and interaction.